In vivo enzyme activity and induction of DNA damage in Swiss albino male mice by automobile waste leachate (UNED Research Journal, 2018)
The rapid growth of motor vehicles use, together with poor waste disposal, produce environmental and biological threats. We evaluated the genotoxicity and enzyme activity of simulated automobile waste leachate in Swiss albino male mice (Mus musculus). Four mice per group were intraperitoneally treated with four leachate concentrations (10%, 15%, 20% and 25% v/v: simulant (IOASL)/distilled water), as well as a negative control (0.5mL UILSL); and a positive control (cyclophosphamide 20mg/Kg body weight) for five consecutive days. There was a concentration-dependent increase in sperm abnormality compared to the negative control (except at 10% and 15%; p
Keywords: automobile waste leachate; micronucleus; enzyme activities; sperm morphology; Ipata Oloje